The progress of redemption from Creation to the New Jerusalem - VanGemeren, Willem A. (Carlisle, UK Paternoster, 1995)
Includes bibliographical references and index.
Keywords: Salvation -- Biblical teaching; Bible -- history of Biblcal events; Bible -- theology; History (theology) -- Biblical teaching